Efficacy of preoperative prophylactic application of betamethasone on postoperative nausea and vomiting in patients undergoing total knee arthroplasty: a prospective randomized controlled trial - Sun, Xiaobo; Dou, Qunli; Li, Bowei; Bai, Guoyang; Qin, Kai; Ma, Jianbing; Yao, Fudong; Huang, Yuanchi (Frontiers in Medicine, 2024)
The demand for total knee arthroplasty (TKA) is increasing, yet postoperative nausea and vomiting (PONV) significantly hinder patient recovery. Preoperative prophylactic administration of glucocorticoids can alleviate PONV, with betamethasone showing promising results in breast and cardiac surgeries. However, its efficacy in TKA patients remains unclear. This study evaluates the efficacy and safety of preoperative betamethasone for PONV in TKA patients through a prospective randomized controlled trial (RCT). In this trial, 124 patients were randomly assigned to receive either 2mL of normal saline (control group) or 2mL of betamethasone sodium phosphate (10.52mg total dose; experimental group) 10 minutes before anesthesia induction. Primary outcomes included nausea severity, vomiting frequency, and antiemetic use, while secondary outcomes were pain scores, knee range of motion, blood glucose, IL-6, CRP, ESR, and adverse reactions. Results showed the experimental group had significantly lower nausea severity at 2h, 4h, 6h, 12h, and 24h post-surgery compared to controls. The average frequency of vomiting in the experimental group (0.060 ± 0.307) was lower than that in the control group (0.390 ± 0.662), with a statistical difference (P < 0.001). The postoperative use of metoclopramide in the experimental group (0.480 ± 2.163) was lower than that in the control group (4.520 ± 6.447), and there was a statistical difference between the two groups (P < 0.001). CRP in the experimental group on the second day after surgery (45.741 ± 47.044) was lower than that in the control group (65.235 ± 50.970), with a statistical difference (P = 0.014). IL-6 in the experimental group was lower on the first (51.853 ± 67.202) and second postoperative days (25.143 ± 31.912) than that in the control group on the first (79.477 ± 97.441) and second postoperative days (38.618 ± 36.282), with statistical differences (P = 0.039, P = 0.006). There was no significant difference in postoperative knee pain, knee range of motion, blood glucose, ESR, and adverse reactions between the two groups. Our prospective RCT demonstrates that preoperative betamethasone is effective and safe for reducing PONV in TKA patients, suggesting a new clinical approach for prophylactic treatment of PONV post-TKA.